2020
DOI: 10.3390/cancers12092529
|View full text |Cite
|
Sign up to set email alerts
|

DNA FISH Diagnostic Assay on Cytological Samples of Thyroid Follicular Neoplasms

Abstract: Although fine-needle aspiration cytology (FNAC) is helpful in determining whether thyroid nodules are benign or malignant, this distinction remains a cytological challenge in follicular neoplasms. Identification of genomic alterations in cytological specimens with direct and routine techniques would therefore have great clinical value. A series of 153 cases consisting of 72 and 81 histopathologically confirmed classic follicular adenomas (cFAs) and classic follicular thyroid carcinomas (cFTCs), respectively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 138 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, the Afirma gene expression classifier (GEC) represents another commonly used molecular test for indeterminate thyroid proliferations, which is based on the opposite concept to predict and "rule in" benign diagnoses [37,[83][84][85][86][87][88][89][90][91][92][93][94][95]. In 2012, Alexander et al introduced the Afirma GEC was firstly analyzed in a key study including 265 indeterminate thyroid lesions out of 4812 FNAC cases from a multicenter trial [37].…”
Section: Aus/flusmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the Afirma gene expression classifier (GEC) represents another commonly used molecular test for indeterminate thyroid proliferations, which is based on the opposite concept to predict and "rule in" benign diagnoses [37,[83][84][85][86][87][88][89][90][91][92][93][94][95]. In 2012, Alexander et al introduced the Afirma GEC was firstly analyzed in a key study including 265 indeterminate thyroid lesions out of 4812 FNAC cases from a multicenter trial [37].…”
Section: Aus/flusmentioning
confidence: 99%
“…However, in several studies, indeterminate nodules with oncocytic predominance were defined by a lower specificity or higher false positive rate in GEC tests. [83][84][85][86][87][88][89][90][91][92]. Brauner et al included a cohort of 122 oncocytic predominant nodules identified as GEC suspicious but resulting in benign pathologies.…”
Section: Follicular Neoplasm (Fn/sfn)mentioning
confidence: 99%
See 3 more Smart Citations